The impact of different operating conditions on membrane fouling and EPS production - Dvořák, Lukáš; Gómez, Marcel; Dvořáková, Markéta; Růžičková, Iveta; Wanner, Jiří (Bioresource technology, 2011)
The main goal of this research was to investigate how different factors influence membrane fouling. The impact of the different concentrations of activated sludge and the amount of extracellular polymer substances (EPS) were monitored. Two pilot plants with submerged membrane modules (hollow fiber and flat sheet) were operated and the raw wastewater was used. Humic substances were identified as the major components of EPS in the activated sludge (more than 34%) in both pilot plants. As the basic constituent in permeate, humic substances were identified as the most dominant components in the effluent (61%) in both pilot plants. Conversely, proteins were mostly analyzed in permeate and supernatant below the detection limit. The total amount of EPS [mgg(-1) (VSS)] was similar for concentrations of activated sludge 6, 10 and 14 g L(-1). Carbohydrates were identified as the component of EPS which tends most to clog membranes.
Keywords: Biofouling; měření biologické spotřeby kyslíku; Biopolymers; membrány umělé; biopolymery; Pressure; rozpustnost; tlak; pilotní projekty; Pilot Projects; Waste Disposal, Fluid; Kinetics; bioznečištění; Membranes, Artificial; Extracellular Space; Solubility; kvartérní amoniové sloučeniny; odpad tekutý - odstraňování; Quaternary Ammonium Compounds; kinetika; Biological Oxygen Demand Analysis; extracelulární prostor